Demosthenes, "Gegen Aristokrates" : Einleitung, Text, Übersetzung und Kommentar - Demosthenes (Texte und Kommentare, 2022)
Demosthenes' speech Against Aristocrates (or. 23) was written for a paranomy trial in which the plaintiff sought to prove that a decree requested in favour of the mercenary leader Charidemos, who was in the service of the Thracian king Kersobleptes, was unlawful. Up to now, it has mainly been of interest to ancient historians and legal historians as a source for the history of Thrace in the first half of the 4th century and as a collection of archaic legal texts. In classical philology, on the other hand, it has not met with a great response - probably also because it presents its readers with obstacles that are difficult to overcome without suitable aids. The present commentary, supplemented by text and translation, attempts to facilitate access to a rhetorically brilliant speech that deserves a wider audience by providing detailed linguistic and contextual explanations, including a critical analysis of the sometimes complicated train of thought